1996
DOI: 10.1006/dbio.1996.0288
|View full text |Cite
|
Sign up to set email alerts
|

Fertilization Stimulates an Increase in Inositol Trisphosphate and Inositol Lipid Levels inXenopusEggs

Abstract: Previous experiments from our lab have suggested that the hydrolysis of phosphatidylinositol 4,5-bisphosphate (PIP2) is required for sperm-induced egg activation in Xenopus laevis. Here we measure the endogenous production of both Ins(1,4,5)P3 and PIP2 during the sperm-induced and ionomycin-induced calcium wave in the egg and find that both increase following fertilization. Ins(1,4,5)P3 increases 3.2-fold from an unfertilized egg level of 0.13 pmole per egg (0.29 microM) to a peak of 0.42 pmole per egg (0.93 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 0 publications
3
57
1
Order By: Relevance
“…If this large 48 pmol increase in DAG was produced through PLC hydrolysis of PIP2, one might expect more PIP2 present during Xenopus fertilization (?1 pmol/cell) (45). Further support for the large DAG increase deriving from PC, not PIP2, hydrolysis is the timing: we found that the IP3 (and thus, PIP2-derived DAG) production peak was much earlier (5 min) than that of the larger DAG (?12 min).…”
Section: Source Of Dag Increase During Fertilizationsupporting
confidence: 50%
See 3 more Smart Citations
“…If this large 48 pmol increase in DAG was produced through PLC hydrolysis of PIP2, one might expect more PIP2 present during Xenopus fertilization (?1 pmol/cell) (45). Further support for the large DAG increase deriving from PC, not PIP2, hydrolysis is the timing: we found that the IP3 (and thus, PIP2-derived DAG) production peak was much earlier (5 min) than that of the larger DAG (?12 min).…”
Section: Source Of Dag Increase During Fertilizationsupporting
confidence: 50%
“…By comparing the time course and size of the increase in DAG mass to the increase in IP3 mass at fertilization [the IP3 increase is about 280 times lower and peaks ?5-10 min before that of DAG; (7,8)], and considering that precursor PIP2 mass is never greater than 2 pmol per Xenopus zygote (45), production of 48 pmol of DAG from PIP2 would be unlikely (9). Because choline mass increases on a magnitude equivalent to the increase in DAG, we suggested that breakdown of PC by phospholipase D (PLD) is the source of DAG (9).…”
Section: Lipid Signaling Related To Fertilizationmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, the degradation of IP 3 R type 1 that is observed in eggs following sperm entry is an indication of IP 3 production (Brind et al, 2000;Jellerette et al, 2000), since it is well documented in somatic cells that IP 3 R type 1 degradation only occurs as a consequence of IP 3 binding (Bokkala and Joseph, 1997;Oberdorf et al, 1999). In this context, it is worth noting that monitoring of IP 3 production in single mammalian zygotes is still not technically possible, although increases in intracellular IP 3 levels have been detected after fertilization in sea urchin and Xenopus laevis eggs (Stith et al, 1993;Snow et al, 1996;Lee and Shen, 1998;Sato et al, 2000;Kuroda et al, 2001) and after injection of porcine sperm extracts into Xenopus eggs (Wu et al, 2001b (Swann, 1992;Ayabe et al, 1995;Yue et al, 1995;Machaty et al, 1997). However, the physiological significance of RyR-mediated [Ca 2+ ] i oscilla-tions is questionable, since they do not lead to full egg activation (Ayabe et al, 1995;Fissore et al, 1995;Wu et al, 1997), and because inhibition of this receptor does not perturb fertilization-induced egg activation (Ayabe et al, 1995).…”
Section: Fertilization and Inositol 145-trisphosphate (Ip 3 ) Produmentioning
confidence: 99%